Burocratas de nível de rua ou elites? Aspectos estruturais e recrutamento na Defensoria Pública brasileira - Jesus, Gustavo Alves de (2023)
The present work analyzes the process of structuring the Brazilian Public Defender's Office and the recruitment of public defenders considering the changes brought about by Constitutional Amendment n° 80/2014, which claims to be the institution “an expression and instrument of the democratic regime”. The function of the defender is the object of analysis according to the theories of elites and bureaucracy at the street level, in order to subsequently assess the possible effects of the framework on the public policy of access to justice. The topic gains relevance when considering the expansion of the institution to all jurisdictional units, unfinished, but expected to occur by the end of 2022. Added to this is the reduced number of studies on the institution with the potential to serve approximately 80 % of the Brazilian population. To promote exploratory research, primary and secondary databases were used. The formation of the primary database had 706 questionnaires, resulting in a confidence level of 95% and a margin of error of 3.5%, while the secondary database had the participation of all general public defenders and through surveys with all public defenders and 3,134 responses, resulting in a survey with a confidence level of 95% and a margin of error of 1.3%. Respondents were asked about their socio-demographic profile and their perception of the structure of the Public Defender's Office, stating that the institution is made up mostly of white people, from high-income families and with a high level of education. Defenders are part of elites in a broad sense, but only part of the members make up political elites, being street-level bureaucrats by nature. Thus, the results on the inadequacy of work structure, workload and reflections on care are relevant, with the first two items being associated with each other.